Financial Performance Determinants in Indonesian Food and Beverage Manufacturing Firms: Faktor-Faktor Penentu Kinerja Keuangan pada Perusahaan Manufaktur Makanan dan Minuman di Indonesia - Devi Prameswari; Eny Maryanti (Indonesian Journal of Law and Economics Review, 2025)
General Background Financial performance assessment remains central in evaluating corporate sustainability amid increasing industrial competition. Specific Background Manufacturing firms in the Indonesian food and beverage sub-sector face distinct operational characteristics that require empirical evaluation using financial indicators. Knowledge Gap Prior studies show inconsistent findings regarding leverage, firm age, firm size, managerial ownership, and intellectual capital in explaining financial performance, particularly within sector-specific contexts. Aims This study examines the association between leverage, firm age, firm size, managerial ownership, and intellectual capital with financial performance measured by Return on Assets. Results Using multiple linear regression on 45 firm-year observations from 2018–2020, firm age and intellectual capital demonstrate significant relationships with financial performance, while leverage, firm size, and managerial ownership show no statistical significance. Novelty The study integrates firm age and intellectual capital within a unified empirical framework focused on the food and beverage manufacturing sub-sector. Implications The findings provide empirical insights for investors and corporate managers in understanding key financial performance determinants within resilient consumer goods industries. Keywords: Financial Performance, Leverage, Firm Age, Intellectual Capital, Food and Beverage Industry Key Findings Highlights: Older firms exhibit stronger profitability patterns within the observed period. Knowledge-based assets contribute meaningfully to asset-based returns. Capital structure and ownership characteristics show limited explanatory power.